REALIZATION OF TRAINING PROGRAMME ON THE BASIS OF LINGUISTIC DATABASE FOR AUTOMATIC TEXTS PROCESSING SYSTEM - M. A. Makarych (Системный анализ и прикладная информатика)
Due to the constant increasing of electronic textual information, modern society needs for the automatic processing of natural language (NL). The main purpose of NL automatic text processing systems is to analyze and create texts and represent their content. The purpose of the paper is the development of linguistic and software bases of an automatic system for processing English publicistic texts. This article discusses the examples of different approaches to the creation of linguistic databases for processing systems. The author gives a detailed description of basic building blocks for a new linguistic processor: lexical-semantic, syntactical and semantic-syntactical. The main advantage of the processor is using special semantic codes in the alphabetical dictionary. The semantic codes have been developed in accordance with a lexical-semantic classification. It helps to precisely define semantic functions of the keywords that are situated in parsing groups and allows the automatic system to avoid typical mistakes. The author also represents the realization of a developed linguistic database in the form of a training computer program.